Disease-Related Stigma, Emotional Regulation and Depression in Patients with HIV - Fozia Bibi, Saima Majeed, Sadia Nikhet, Bisma Jamil Makhdoom, Ali Burhan Mustafa (Pakistan Journal of Medical & Health Sciences, 2024)
Background: HIV/AIDS has become one of the major global health burdens. Self-stigma and emotion dysregulation in people living with HIV (PLWH) have become urgent issues and have attracted the attention of both physicians and epidemiologists. Aim: To examine the relationship between disease-related stigma, emotional regulation, and depression in patients with HIV. Method: A cross-sectional study was conducted. A purposive sample of 100 patients—70 male and 30 female diagnosed with HIV/AIDS was collected from two public hospitals in southern Punjab. Patients who had been diagnosed as being HIV positive for at least three months were included in the study. The age range of participants was 18 to 50 years. Patients with other medical issues were excluded from the study. Measures for data collection were the Discrimination and Stigma Scale (DISC), Difficulties in Emotional Regulation Scale (DERS), and Hamilton Depression Scale. The data was evaluated using SPSS version 24. Pearson’s correlation was applied. Results: There is an inverse relationship (-.34**) obtained between disease-related stigma and emotional regulation, whereas a significant positive relationship (r =.41**) is found between disease-related stigma and depression. A negative relationship (r=-.59**) is also examined between emotional regulation and depression. Emotional regulation is a mediator between disease-related stigma and depression in patients with HIV. There is a significant gender difference in depression. The mean score of depression is high among females as compared to males. Practical Implication: It improved the psychological health of HIV-positive patients by categorizing the issues they face. Conclusion: It was concluded that disease-related stigma is positively related to depression while emotional regulation is inversely related to depression. Emotional regulation also plays a mediating role between self-stigma and depression in patients with HIV positive. Women scored higher on depression as compared to men. Keywords: HIV Patients, Psychological Impact, Psychological Distress and Social Stigma.